PENGUKURAN ANTROPOMETRI UNTUK DESAIN PERALATAN YANG TERKAIT DENGAN TELINGA : SEBUAH SURVEI PENDAHULUAN - Umami, Mahrus K (SENATIK STT Adisutjipto, 2017)
This study is a preliminary survey of a main study on anthropometry of ear. This study was done since the availability of ear anthropometry for Indonesian population was very limited. On the other, the availability of the ear anthropometry is very important. The current study aims to collect anthropometric data that are possible to consider in designing ear-related products. Thirty subjects aged in the range of 18-20 years old were involved in the measurement. Three dimensions of the outer ear, namely: ear hole length, ear connection length, and pinna length were measured. Result of this study shows an initial description of the outer ear dimensions that is useful in designing ear-related products, especially for Indonesian young adults.